PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN PURWOSASONO DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , MUHAMMAD GUNAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Situation mapping is measurement and mapping of an area using the particular methods in accordance with a set of technical work and present condition of the horizontal and vertical objects of the earth in the mapping area. Mapping the situation in order to make a situation map in 1 : 500 scale of Dusun Purwosasono, Desa Beluk, Kecamatan Bayat, Kabupaten Klaten, Provinsi Jawa Tengah, using the method of teretris measurement. Data collection and processing is using digital method by software Surpac and Arc gis. Measurement were carried out include horizontal control framework, vertical control framework and the detail of the situation, overall measurement have to be match to the Term Of Refrences. The result is a situation map in 1:500 scale. The map test by using 33 samples data, that were 13 distance data, 13 vertical detail data, and 7 field objects data, samples match to teh field reality.